Effects of xylano-pectinolytic enzymes by Bacillus subtilis ADI1 on biobleaching of kenaf (Hibiscus cannabinus L.) Pulp - Mohd Nawawi, Muhammad Hariadi (2016)
Kenaf (Hibiscus cannabinus) is an annual non-wood plant which has shown great potential as an alternative source of papermaking fibre. In the pulp and paper industry,due to growing public concern about the environment, technological changes in the bleaching processes have been rising. The use of chemical additives during bleaching process to improve the brightness of paper causes the effluent to contain some chlorinated organic compounds that have shown mutagenicactivity. The use of combined xylanase and pectinase in pulp bleaching may assist in enhancing the brightness of paper and could reduce harmful pectins produced in the effluent and thus rendering a more eco-friendly papermaking process as well as improvements in the paper quality. The aim of this research was to study the production of xylano-pectinolytic enzymes from a bacterial isolate Bacillus subtilis ADI1 and to examine the effectiveness of using xylano-pectinolytic enzymes on kenaf pulp in biobleaching. The characteristics of enzymes being sought in papermaking are higher production, higher optimal pH and temperature, good stabilities under these conditions and finally a low associated cellulase production. Bacillus subtilis ADI1, as the potentially high extracellular xylanase and pectinase producer, was isolated from composting and rotting area around UPM Serdang, Malaysia (Biorefinery Complex, UPM, Selangor). The effects of pH, temperature, inoculum concentration, agitation speed and concentration of rice bran on xylanase and pectinase production were studied. Optimum pH and temperature for xylano-pectinolytic enzymes production by Bacillus subtilis ADI1 was at pH 8 and 50°C. Highest xylanase and pectinase production was from 3% (v/v) inoculum concentration and agitation speed of 200 rpm. Maximum xylanase and pectinase production was obtained from 3% (w/v) of rice bran while higher and lower concentration of rice bran resulted in poor enzyme production. Bacillus subtilis ADI1 is an alkalophilic thermotolerant bacteria which under optimal cultural conditions, can produce 5.25 times more xylanase and 1.6 times more pectinase than prior to optimisation study (non-optimized condition). Meanwhile, the xylano-pectinolytic enzymes stabilities were studied at optimal pH and temperature for enzyme activities. Xylano-pectinolytic enzymes of Bacillus subtilis ADI1 resulted in the optimum conditions of pH 8 and temperature 50°C. The enzymes showed considerable thermostability (stable up to 2 to 3 hours at 40°C) and pH stability (stable up to 3 hours at pH 8). Thus, xylano-pectinolytic enzymes of Bacillus subtilis ADI1 are suitable for application in biobleaching of pulp. Optimal enzymatic processes were studied, the xylanase-pectinase doses required in biobleaching pretreatment were 15 and 7.5 U/g of oven dried pulp, and the effective retention time needed for pretreatment was 180 min. The optimised enzymatic processes significantly improved the pulp properties and showed that the ISO brightness increased from 71.14% (untreated) to 84.18% (treated)and reduced the chlorine consumption by 15.5% reduction. In conclusion, xylanopectinolytic enzymes from Bacillus subtilis ADI1 showed interesting biotechnological characteristics that are suitable for application in pulp and paper industry.